Identification of Morphological Characteristics of Sidimpuan Snake Fruit (Salacca sumatrana Becc.) - Edih Nasution, Halida; Rasmita Adelina; Yusriani Nasution; Nuzul Hijri Darlan; Sutan Pulungan (International Journal of Natural Science Studies and Development (IJOSS), 2025)
Sidimpuan snake fruit (Salacca sumatrana Becc.) plants have several varieties, one of which has a distinctive feature in the taste and colour of the fruit flesh. The results of the study from the three locations in Padangsidimpuan City obtained the morphological characteristics of sweet snake fruit (less) having a round oval to long triangular shape with brown to yellowish-brown fruit skin colour. The results of the dendrogram of the sidimpuan snake fruit (Salacca sumatrana Becc) kinship relationship based on the morphological characters of five types of salak, namely sweet snake fruit(less), sweet snake fruit (moderate), sweet snake fruit, white snake fruit, and red snake fruit, obtained 3 clusters from each location. Lubuk Raya Village, the Sidimpuan snake fruit kinship relationship based on five types of snake fruit, has a similarity level of 84 %. Batu Layan Village, the Sidimpuan snake fruit kinship relationship based on five types of snake fruit, has a similarity level of 92 %, and Palopat Maria Village, the Sidimpuan snake fruit kinship relationship based on five types of snake fruit, has a similarity level of 96 %. The results of the identification of morphological characters of snake fruit from three research locations based on the morphological characters of five types of snake fruit show genetic similarities, namely in the shape of the stem, leaf shape, upper leaf colour, lower leaf colour, leaf sheath colour, thorn colour, flower colour, fruit shape, and fruit skin colour